Apagamento e alternância b/v em documentos manuscritos do século XVIII - Renata Ferreira Costa (Filologia e Linguística Portuguesa, 2005)
This paper intends to examine ocurrences of letters extinguishing phenomena, as aphaeresis and syncope, in documents manuscripts of the century XVIII. It also shows cases of alternation between the consonants and <v>.